Peningkatan Pemahaman Konsep Himpunan Siswa SMP Melalui Media Pembelajaran Berbantuan Web Centric Course - Dhimas Ari Prassethiyo; Marhan Taufik; Ummah, Siti Khoiruli (JRPM (Jurnal Review Pembelajaran Matematika), 2024)
This study analyzed the effect of using Web Centric Course-assisted learning media on students' understanding of mathematical concepts. The effect was measured by the improvement of the test result. The study was conducted based on the fact that teachers and students need learning media using websites because it does not need application installation. The subjects of this study were 32 students of class VIII. This research is a Pre-Experimental Design with the form of One-Group Pretest-Posttest Design. The analysis technique used is the normality test, variance homogeneity test, t-test, and the N-Gain test. Based on the results of the t-test analysis on the pretest and posttest data of the experimental class, the Sig. (2-tailed) of 0.000 <0.05 which means there is a significant difference between before and after treatment. It can be concluded that the Web-Centric Course (X) assisted learning media significantly affects the understanding of mathematical concepts in class VIII students (Y).